Lo spazio del ruolo. La prospettiva di una docente giusinternazionalista counselor - Lupone, Angela Maria Gabriella (Milano University Press, 2022)
The book is a contribution, on one side, to the ongoing reflexion and sharing of best practices on student centred teaching and cooperative learning in higher education and, on the other and widely speaking, on role management or effective leadership models in the pedagogical and organisational University context. It addresses teachers from all the disciplines and students. Based on, and moving from, the author's personal experience as an international law scholar, this work suggests different possible perspectives in disclosing disciplinary literacy, eg the legal one, through the lens of relational competencies. The fil rouge across the book is role awareness, i.e. the ability to understand the space of the role (as well as sovereignty in international relations) as an area to fill and, if pertaining to others, as a zone to respect. Nevertheless, within this perspective and setting as starting point the fact that the ultimate task of every teacher, and university professor, is blending all the forms of knowledge in the service of effective instruction, thus aiming at accompanying classes not only in assimilating (international law) knowledge, but also competencies, the author explores if an experience-based relational training of teachers can have a transformative and improving effect on the teaching methodology, within an approach that seeks to change the focus from teaching to learning. In the systemic frame and linked to the field of international law and relations, the space of the role overlaps with the notion of sovereignty, as well as with the nature of the International Community as an interdependent, original, necessary and (formally) equal society. Interpersonal and international relations thus seem to be traced back to a common system.